A mass spectrometry method for sensitive, specific and simultaneous detection of bovine blood meal, blood products and milk products in compound feed. (15th April 2018) - Lecrenier, M.C.; Planque, M.; Dieu, M.; Veys, P.; Saegerman, C.; Gillard, N.; Baeten, V.
Highlights: A multi-target LC-MS/MS method to detect bovine by-products in feed was developed. The method reaches the LOD required by the legislation into force (0.1%). The method is fast and easy to use, making it suitable for a routine implementation. Concatamers (conCAT) were designed to be used as internal standard. Abstract: Feed sustainability is one of the biggest challenges for the next few years. Solutions have to be found that take feed quality and safety into account. Animal by-products are one valuable source of proteins. However, since the bovine spongiform encephalopathy (BSE) crisis, their use has been strictly regulated. The objective of this study was to propose a routine, sensitive and specific method using ultra-high performance liquid chromatography coupled to tandem mass spectrometry for the detection of blood-derived products and milk powder in feed. Contaminated aquafeeds were analysed in order to evaluate the sensitivity and specificity of the method. This new method meets both selectivity and sensitivity (0.1% (w/w)) requirements imposed by the European Commission for animal proteins detection methods. It offers an innovative and complementary solution for the simultaneously identification of authorised and unauthorised animal by-products such as processed animal proteins (PAPs).